Multi-omics analysis identifies glioblastoma dependency on H3K9me3 methyltransferase activity - Qiqi Xie; Yuanning Du; Sugata Ghosh; Saranya Rajendran; Aaron A. Cohen-Gadol; José-Manuel Baizabal; Kenneth P. Nephew; Leng Han; Jia Shen (npj Precision Oncology)
Abstract Histone H3 lysine 9 dimethylation and trimethylation (H3K9me2/3) are prevalent in human genomes, especially in heterochromatin and specific euchromatic genes. Methylation of H3K9 is modulated by enzymes such as SUV39H1, SUV39H2, SETDB1, SETDB2, and EHMT1/2, which influence cancer progression. This study reveals differential expression of these six H3K9 methyltransferases in tumors, with SUV39H1, SUV39H2, and SETDB1 showing significant links to cancer phenotypes. We developed the “H3K9me3 MtSig” (H3K9me3 methyltransferases signature) based on these findings. H3K9me3 MtSig is unique to various tumors, with prognostic significance and associations with key signaling pathways, especially in glioblastoma (GBM). Elevated H3K9me3 MtSig was observed in GBM samples, correlating with the G2/M cell cycle and reduced immune responses. H3K9me3-mediated repetitive sequence silencing by H3K9me3 MtSig contributed to these phenotypes, and inhibiting H3K9me3 MtSig in patient-derived GBM cells suppressed proliferation and increased immune responses. H3K9me3 MtSig serves as an independent prognostic factor and potential therapeutic target.